Psychosocial Adjustment of In-Home Caregivers of Family Members with Dementia and Parkinson’s Disease: A Comparative Study - María Cristina Lopes Dos Santos; María Victoria Navarta-Sánchez; José Antonio Moler; Ignacio García-Lautre; Sagrario Anaut-Bravo; Mari Carmen Portillo (Parkinson's Disease)
Neurodegenerative diseases such as Parkinson’s and dementia are highly prevalent worldwide. People who suffer from these disorders often receive in-home care and assistance from family members, who must dedicate a considerable amount of time to the care recipient. The study of family caregivers’ psychosocial adjustment to the degenerative processes of both conditions is of interest due to the implications for the quality of life of both the care receiver and the caregiver, as well as other family members. This study compares the psychosocial adjustment of family members who care for people with dementia and Parkinson’s disease and identifies the main sociodemographic variables that affect the processes of adjustment to both conditions. To this end, the Psychosocial Adjustment to Illness Scale (PAIS-SR) and a sociodemographic form were administered to 157 family caregivers in Navarre, Spain. The results show that adjustment to the disease in family caregivers of people with Parkinson’s disease and dementia is, in general, satisfactory and related to variables such as place of residence, income, and employment status. The illness itself (Parkinson’s or dementia), however, is found to be the most influential variable in the level of psychosocial adjustment.